The Final Problem: Constructing Coherence in the Holmesian Canon - Ulleland Hoel, Camilla (Authorship, 2017)
The death and resurrection of Sherlock Holmes, a contrarian reading in which Holmes helps the murderer, and the century-long tradition of the Holmesian Great Game with its pseudo-scholarly readings in light of an ironic conviction that Holmes is real and Arthur Conan Doyle merely John Watson’s literary agent. This paper relies on these events in the afterlife of Sherlock Holmes in order to trace an outline of the author function as it applies to the particular case of Doyle as the author of the Sherlock Holmes stories. The operations of the author function can be hard to identify in the encounter with the apparently natural unity of the individual work, but these disturbances at the edges of the function make its effects more readily apparent. This article takes as its starting point the apparently strong author figure of the Holmesian Great Game, in which “the canon” is delineated from “apocrypha” in pseudo-religious vocabulary. It argues that while readers willingly discard provisional readings in the face of an incompatible authorial text, the sanctioning authority of the author functions merely as a boundary for interpretation, not as a personal-biographical control over the interpretation itself. On the contrary, the consciously “writerly” reading of the text serves to reinforce the reliance on the text as it is encountered.The clear separation of canon from apocrypha, with the attendant reinforced author function, may have laid the ground not only for the acceptance of contrarian reading, but also for the creation of apocryphal writings like pastiche and fan fiction.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE4MjUvYWoudjZpMS40ODM2